The quality of outreach workers and the services they provide for the NSEP program in Malaysia - Baba, Ismail; Azman, Azlinda (2014)
The outreach workers have been the focal point for the success and failure of the NSP in Malaysia. They are the back bone and the front line workers of the program.The program that was introduced in 2006 and has succeeded in reducing the number of HIV infections among people who inject drugs (PWID).In a recent study by the Centre of Excellence for Research in AIDS (CERiA) at the University of Malaya and the Kirby Institute, University of New South Wales on harm reduction programs that the Malaysian government has saved RM47.1 million in direct health care costs that include treatment and monitoring.This is to demonstrate that harm reduction programs in Malaysia are highly cost-effective.The outreach workers faced many challenges while providing services to PWID. They often have to face with stakeholders who are completely rejected or give very little support to the NSP. Additionally, they also have to face with stigma and discrimination due to the work they do. For the outreach workers who are ex-PWID this is an occupationally hazard job for them.If they are not strong emotionally, psychologically and socially they can easily revert back to their old habit of injecting drugs.For the outreach workers who are new to the job, naïve and inexperienced they often being manipulated by PWID.All these could lead to burnout.So far very little studies have been done to examine the role of the outreach workers in providing NSP in Malaysia or anywhere else in the world. If the outreach workers remain to be the backbone of the NSP we need to know how well they cope with the work and what are the challenges they have faced in delivering NSP.A qualitative study that involved 16 outreach workers and three focus group discussions (FGD) were conducted in the northern part of Malaysia. The findings suggested that we need to redefine the role the outreach workers in NSP.If Malaysia were to expand its NSP nationwide, she has to take the outreach workers seriously.A proper standard and training must be set up in order to improve quality of the NSP.Their social well of the outreach workers being must be properly addressed. Furthermore their role can be expended to the Methadone Maintenance Therapy (MMT) program in order provide better service to PWID.